Analysis on ASM Method Perfomance in Solving Fuzzy Transportation Problems - Anggraini, Dini Putri; Sawaluddin (Journal of Mathematics Technology and Education, 2022)
This study aims to show the performance of the ASM method on transportation problem. The transportation problem relates to the distribution of a product from several sources, with limited supply, to several destinations, with a certain demand, in order to obtain the minimum transportation costs. However, the amount of supply and demand cannot always be known with certainty and may change from time to time. In this paper, the coefficient of supply and demand uses fuzzy numbers and uses the ASM method to determine the optimal solution both to minimize costs and maximize profits. The result is that with the ASM method, the balanced transportation problem is always optimal, while the unbalanced transportation problem is not always optimal.